IMPLEMENTATION OF HAPTIC CONTROL IN A ROBOTICS SYSTEM FOR REMOTE SURGERY - Togar Timoteus Gultom; Ajub Ajulian ZM; Siri Lek (Journal of Moeslim Research Technik, 2025)
The advancement of telemedicine and robotic surgery has led to increased interest in haptic feedback systems, which enhance the surgeon's ability to perform remote procedures. Haptic technology provides tactile sensations, allowing surgeons to feel the instruments' interactions with tissues, thus improving precision and control during surgery. This research aims to implement haptic feedback in robotic surgical systems, evaluating its impact on surgical performance and user experience during remote operations. The study seeks to determine whether incorporating haptic feedback can enhance the effectiveness and safety of robotic-assisted surgeries. A mixed-methods approach was employed, combining hardware development of a robotic surgical system with haptic feedback integration. Surgeons participated in controlled experiments to perform simulated surgical tasks with and without haptic feedback. Performance metrics, including task completion time, accuracy, and user satisfaction, were assessed. The implementation of haptic feedback resulted in a 30% reduction in task completion time and a 25% improvement in accuracy compared to non-haptic conditions. Surgeons reported higher satisfaction levels and increased confidence in performing procedures with the haptic-enabled system. The findings indicate that integrating haptic feedback into robotic surgical systems significantly enhances surgical performance and user experience. This research contributes to the growing body of knowledge in robotic surgery, demonstrating the potential of haptic technology to improve outcomes in remote surgical procedures.